Integrated Approach to Diagnosis of Associated Occupational Asthma and Rhinitis. Issue 6 (2012) - Nguyen, Sébastien; Castano, Roberto; Labrecque, Manon
Abstract : Patients with coexisting work-related rhinitis and asthma would benefit from an adequate and simultaneous recognition of both diseases. The present case illustrates the advantages and importance of using an integrated approach to confirm a diagnosis of occupational rhinitis (OR) and occupational asthma (OA). A 38-year-old woman, who worked as an animal laboratory technician since 2004, first noticed the appearance of rhinitis and conjunctivitis symptoms in 2007 when she was exposed to rats. A skin-prick test with rat extract was strongly positive. A specific inhalation challenge with parallel assessment of nasal and bronchial responses was conducted. After 10 min of exposure, she developed rhinitis and conjunctivitis symptoms, her forced expiratory volume in 1 s dropped by 27.5% and her nasal volume, measured by acoustic rhinometry, decreased by 80% from baseline values. After allergen exposure, induced sputum and nasal lavage examination demonstrated an increase in eosinophils (11% and 20%, respectively). A diagnosis of associated allergic OA and OR was confirmed and she was advised to stop working with rats. A systematic and parallel diagnostic approach enables confirmation of a diagnosis of OA and OR in patients complaining of work-related rhinitis and asthma symptoms.